The Monographic Sociology of Dimitrie Gusti - Rostás, Zoltán (Eastern European Countryside, 2024)
This paper briefly presents the method of sociological monography conducted by the Romanian professor Dimitrie Gusti – from its emergence, through its theoretical foundation and application in field research, until its prohibition. The paper explores, step by step, the development of the specific monograph methodology, followed by its introduction in university studies and in the practice of social intervention. The Bucharest Sociological School that was formed around the monographic field research in the 1930s later began to diversify, but its extinction was due to World War II and to the establishment of the communist regime.